GERAKAN LSM KOLING PADA UPAYA KONSERVASI HUTAN DIENG TAHUN 2000-2010 - Muntobingul Rojbiyah (Jurnal Sosiologi Reflektif, 2013)
The emergence of various kinds of natural disasters in many parts of the world indicates just how nature has been corrupted and degraded. Environmental degradation that occurs has a lot of movement attracted the attention of environmentalists as well as NGOs. Concern about environmental issues today is nothing new among NGOs. A variety of environmental movement they are doing to realize a sustainable environment. Similarly, NGOs Koling which since 1999 has been struggling in Wonosobo forest management policy. Ideology of the NGO movement is a determination of how they develop strategies and activities in the struggle for environmental issues (forestry) in Wonosobo.With the sociological perspective of social movement paradigm, the research made to analyze how the paradigm of the NGO movement Koling determine the pace of movement is then presented to each program and activity does. The theory used to analyze the theoretical model with the environmental NGO movement Hayden and Mansour Fakih ideas about the paradigm of NGOs. The final results concluded that: (1) NGO environmental movement Koling is visionary in achieving management natural resources (especially the management of forest resources) based on the empowerment and social welfare, (2) the movements are more likely paradigmatic moderate/reformist despite sometimes also paradigmatic liberal/ transformative, (3) the analysis of the concept model of the environmental NGO movement Heyden, Koling more closely to the model of instrumental strategies and sub -cultural.